Euphemistic expressions and strategies used by Egyptian speakers of Arabic in light of face theory - Enab, Noha (AUC Knowledge Fountain, 2020)
Euphemism, as a linguistic, pragmatic and cultural phenomenon, plays a vital role in creating harmonious interaction and saving face in social communication. However, limited research was conducted on the use of euphemism in Egyptian Arabic. The present study is geared mainly towards probing into the euphemistic expressions and strategies that Egyptian speakers of Arabic resort to when certain tabooed or sensitive topics and concepts are brought up in daily communication - in both face-threatening and non-face-threatening situations- when addressing topics such as physical and mental impairment, cancer, socially-inferior professions, bodily functions, sensitive marital status for women, as well as, death. A population of 275 adult Egyptian men and women from different ages and educational backgrounds were randomly chosen to answer a questionnaire on the euphemistic expressions they most commonly use in day-to-day life. The questionnaire has tested both face-threatening and non-face-threatening acts. Euphemistic strategies were then deduced and analyzed in the light of the classic categorization done by Allan and Burridge (1991). The findings suggest that Egyptian speakers of Arabic tend to use euphemisms a lot in their daily communication, especially in the presence of face-threatening acts. The most frequently used euphemistic strategies varied according to the addressed topic, but the ones most heavily relied upon were: understatement, general-for-specific, hyperbole, borrowing, circumlocution, and technical jargon. The study recommends promoting understanding and awareness of euphemistic expressions as well as strategies when teaching Arabic as a foreign language - especially Egyptian Arabic- hence more effective and interactive communication between learners and native speakers.